STUDI KOMPARASI PEMBENTUKAN PORTOFOLIO OPTIMAL MENGGUNAKAN MODEL MARKOWITZ DAN MODEL INDEKS TUNGGAL - Agustin, Adelya Tri; Abundanti, Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.05.TAHUN.2023DO - 10.24843/EEB.2023.v12.i05.p01, 2023)
The purpose of this study was to determine the results of the comparison of the formation of the optimal portfolio using the Markowitz model and the Single Index model. This study was conducted on companies that are members of the LQ45 Index in the period August 2017 to January 2020. The number of companies used as samples were 32 companies using a purposive sampling method, namely data selection based on several criteria.  The data were obtained by observing, understanding, and studying books, journals, theses and other literature related to research, as well as from the closing price of each company's shares at Yahoo Finance and idx.co.id.  The data analysis technique used is the Wilcoxon-Mann-Whitney test. The results of this study showed that is no significant difference in the average return of the two models, so it can be concluded that to form an optimal LQ45 stock portfolio, both methods can be used, namely the Markowitz model and the Single Index model. The result of study have implications for the selection of stocks for investors.  Investors can use the Markowitz model and the Single Index model in selecting the optimal portfolio because the two methods are the same but only differ in the calculation.